An Accelerated Step Test to Assess Dancer Pre-season Aerobic Fitness. Issue 1 (March 2014) - Bronner, Shaw; Rakov, Sara
As the technical performance demands of dance increase, professional companies and pre-professional schools are implementing pre-season screenings that require an efficient, cost effective way to measure dancer aerobic fitness. The aim of this study was to assess an accelerated 3-minute step test (112 beats·min -1 ) by comparing it to the well-studied YMCA step test (96 beats·min -1 ) and a benchmark standard, an incremental treadmill test, using heart rate (HR) and oxygen consumption (VO2 ) as variables. Twenty-six professional and pre-professional dancers (age 20 ± 2.02 years) were fitted with a telemetric gas analysis system and HR monitor. They were tested in the following order: 96 step, 112 step, and treadmill test, with rest to return to baseline heart rate between each test. The step and treadmill tests were compared using Intra-class Correlation Coefficients [ICC (3, k)] calculated with analysis of variance (p < 0.05). To determine whether there was a relationship between peak and recovery HR (HRpeak, HRrecov ) and VO2 (VO2peak, VO2recov ) variables, Pearson product moment correlations were used. Differences due to gender or group (pre-professionals versus professionals) were explored with MANOVAs for HRpeak, VO2peak, HRrecov, VO2recov, and fitness category. The 112 step test produced higher HRpeak and VO2peak values than the 96 step test, reflecting a greater workload (p < 0.001). For HRpeak, there were high correlations (r = 0.71) and for HRrecov, moderate correlations (r = 0.60) between the 112 step test and treadmill test. For VO2peak and VO2recov, there were moderate correlations between the 112 step test and treadmill test (r = 0.65 and 0.73). No differences between genders for VO2peak values were found for either step test, but males displayed lower HRpeak values for both step tests and higher VO2peak values during the treadmill test (p < 0.001). Recovery HR was lower in males for the 96 and 112 step tests (p < 0.05). This was reflected in higher fitness scores. There were no differences between groups in any of the variables when only females were compared. For the 112 step test, correlations between HRpeak and HRrecov were high (r = 0.85), and correlations between HRpeak and fitness category were very high (r = 0.98). It is concluded that the 112 step test provides an efficient, acceptable tool for testing dance populations, though further testing in larger groups of dancers representing a diverse range of genres and training levels is needed.